Nuancen des Anthropomorphismus in Waldemar Bonsels’ Mario und die Tiere (1928) - Stefan Hecht (Recherches Germaniques)
The novel Mario und die Tiere (1928) from Waldemar Bonsels shows a spectrum of anthropomorphism which ranges from naive childlike anthropomorphism to the possibility of a theriomorph perspective. Drawing on research of the last decades in behavioral psychology, neuroscience and empathy, this article renders plausible and analyses sequences of human-animal-contacts, where the young hero anthropomorphizes animals.The diagnosis of a natural tendency of humans to anthropomorphize animals, is compared with ambivalent effects of anthropomorphism such as the act of domesticating wild animals. Under recourse to the literary source possibilities are discussed, how a citical applied anthropomorphism could be understood as way for a better understanding of animals without ontologizing them, and not to confuse alterity with inferioity.